2014
DOI: 10.1016/j.matbio.2013.10.007
|View full text |Cite
|
Sign up to set email alerts
|

LTBP-2 competes with tropoelastin for binding to fibulin-5 and heparin, and is a negative modulator of elastinogenesis

Abstract: Latent transforming growth factor-beta-1 binding protein-2 (LTBP-2) is a protein of ill-defined function associated with elastic fibers during elastinogenesis. Although LTBP-2 binds fibrillin-1, fibulin-5, and heparin/heparan sulfate, molecules critical for normal elastic fiber assembly, it does not interact directly with elastin or its precursor, tropoelastin. We investigated the modulating effect of LTBP-2 on two key interactions of tropoelastin during elastinogenesis a) with fibulin-5 and b) with heparan su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…Strongly upregulated Ltbp2 is also an ECM protein principally expressed by all cells of mesenchymal origin. Its function is largely unknown, but it has been found to surround chondrocytes (63), and Ltbp2 might have a negative regulatory impact on the assembly of elastic fibers (54).…”
Section: Discussionmentioning
confidence: 99%
“…Strongly upregulated Ltbp2 is also an ECM protein principally expressed by all cells of mesenchymal origin. Its function is largely unknown, but it has been found to surround chondrocytes (63), and Ltbp2 might have a negative regulatory impact on the assembly of elastic fibers (54).…”
Section: Discussionmentioning
confidence: 99%
“…This interaction might help provide additional anchoring of microfibrils to basal membranes. A recent paper also suggested that LTBP-2 might negatively regulate elastogenesis in cultured ear cartilage cells through its interactions with fibulin-5, heparin, and elastin (Sideek et al 2014). …”
Section: Ltbp-2mentioning
confidence: 99%
“…When LTBP-2 is knocked down, elastin preferentially deposits onto fibrillin-2 microfibrils. Another study showed that LTBP-2 binds fibulin-5 and inhibits tropoelastin-fibulin-5 interaction (Sideek et al, 2013). LTBP-1 binds strongly to fibulin-4 and forms a ternary complex involving LTBP-1, fibrillin-1 and fibulin-4 (Massam-Wu et al, 2010).…”
Section: Fibulin-4 and Fibulin-5 During Elastic Fiber Assemblymentioning
confidence: 99%